Study of physical properties of ice cream soft serve during storage (Research, Society and Development, 2020)
Ice creams are basically composed of: milk protein, sugar, fat, water, emulsifiers, stabilizers, dyes, flavorings and additional ingredients such as chocolate, cookies, wafers, pieces of fruit and nuts, among others. The characteristics of food products change over the shelf-life and can become undesirable. The physical characteristics of the ice cream are influenced according to the composition, and the chosen manufacturing process will directly interfere with the aggregation state of the fat globules, the amount of incorporated air, the size of the air bubbles, the viscosity of the aqueous phase and the size and aggregation status of the ice crystals. Among these quality interferents are also handling and storage conditions. In this study an analysis was carried out about the stability of soft serve ice cream produced from UHT milk drink through the sedimentation and melting index in a period of 0, 60 and 120 days, showing good consumption conditions for all analyzed samples.